1994
DOI: 10.1099/00207713-44-2-330
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Determination of rRNA Genes of Pathogenic Vibrio Species and Whole-Cell Identification of Vibrio vulnificus with rRNA-Targeted Oligonucleotide Probes

Abstract: A comparative analysis of seven new 16s rRNA gene sequences of pathogenic I/ibrio species with previously published vibrio sequences confirmed that Vibrio vulnificus represents a group that is not closely related to the core organisms of the genus Vibrio. In addition, we found that K vulnijicus, Listonella (Vibrio) anguillarum and I/ibrio diazotrophicus branch off separately from the core group. A comparison of the 16s rRNA gene sequences of V. vulniJicus strains belonging to biotypes 1 and 2 revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 21 publications
5
69
0
6
Order By: Relevance
“…No amplification of closely related vibrio or non-vibrio strains were observed, indicating the specificity of the pilF realtime PCR assay ( Table 2). The pilF assay thus contrasts with other targets used to identify pathogenic strains of V. vulnificus, such as 16S rRNA (Aznar et al, 1994;Nilsson et al, 2003;Vickery et al, 2007) and vcgC polymorphisms (Rosche et al, 2005;Warner and Oliver, 2008;Baker-Austin et al, 2010b), which have shown limited usefulness in detecting biotype 2 and biotype 3 V. vulnificus strains potentially dangerous to human health (Roig et al, 2010;Sanjuan et al, 2009). Both biotype 2 (serovar E and serovar I) and biotype 3 V. vulnificus strains represent important human pathogens (Amaro and Biosca, 1996;Bisharat et al, 1999), and the ability to identify potentially virulent strains rapidly is of paramount importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No amplification of closely related vibrio or non-vibrio strains were observed, indicating the specificity of the pilF realtime PCR assay ( Table 2). The pilF assay thus contrasts with other targets used to identify pathogenic strains of V. vulnificus, such as 16S rRNA (Aznar et al, 1994;Nilsson et al, 2003;Vickery et al, 2007) and vcgC polymorphisms (Rosche et al, 2005;Warner and Oliver, 2008;Baker-Austin et al, 2010b), which have shown limited usefulness in detecting biotype 2 and biotype 3 V. vulnificus strains potentially dangerous to human health (Roig et al, 2010;Sanjuan et al, 2009). Both biotype 2 (serovar E and serovar I) and biotype 3 V. vulnificus strains represent important human pathogens (Amaro and Biosca, 1996;Bisharat et al, 1999), and the ability to identify potentially virulent strains rapidly is of paramount importance.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we believe that pilF is a useful and reliable additional target for epidemiological and diagnostic tests alongside other reported assays for virulence testing in V. vulnificus, such as 16S rRNA (Aznar et al, 1994;Nilsson et al, 2003;Vickery et al, 2007), capsular polysaccharide genes (Han et al, 2009), and vcgC and vcgE analysis (Rosche et al, 2005;Baker-Austin et al, 2010b;Warner and Oliver, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Vibrio species are common inhabitants of aquatic environments, and they can be isolated under a wide range of salinity and temperature conditions from oysters, clams, mussels, and fish, as well as from sediment and plankton. 7,8 Some species have been reported to cause infections in humans and aquatic animals, 9,10 whereas a small number of other species have been used as probiotics in aquaculture. 11,12 In the present study, a Gram-negative bacterium (BFLP-10 T ), with inhibitory activity against Vibrio species, was isolated from faeces of wild long-snouted seahorses (H. guttulatus) captured in northwest Spain.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the 16S rRNA gene sequences of V. vulnificus isolated from the environmental and clinical origin is seen to differ by a total of 17 out of 1556 bases, with most of the polymorphism being centered around the first 500 base pairs of the forward strand (Van de Peer et al 1996). A restriction fragment analysis of the polymorphic region has further shown to generate two profiles 16S rRNA typeA or 16S rRNA typeB which significantly correlated respectively to its environmental or clinical origin (Aznar et al 1994;Kim and Jeong 2001;Nilsson et al 2003).…”
Section: Introductionmentioning
confidence: 99%